Use of antirheumatic drugs in covid-19 from hydroxychloroquine to anakinra through tocilizumab and baricitinib: A review of the literature - Salas-Bolaños, Rosa Alejandra (2021)
We are currently in a global pandemic caused by the coronavirus 2019 or COVID-19, presenting different challenges for the health system due to the fact that there is still no vaccine or a treatment that has proven its effectiveness in its entirety, being the management current preventive and supportive. Therefore, this review will study the most prominent antirheumatic drugs that have a probable pharmacological effect, such as hydroxychloroquine, tocilizumab, anakinra and baricitinib, against COVID-19. It is expected that they will provide support for future treatments. and research on the disease.